STRONTIUM-APATITE: NEW OCCURRENCES, AND THE EXTENT OF SR-FOR-CA SUBSTITUTION IN APATITE-GROUP MINERALS - Chakhmouradian A.R.; Reguir E.P.; Mitchell R.H. (My University, 2002)
The paragenesis and compositional variation of strontium-apatite from three new localities are characterized. At Lovozero, in the Kola Peninsula, Russia, strontium-apatite forms elongate crystals and thin reaction-induced rims on early strontian fluorapatite in nepheline syenite pegmatites. The apatite-group minerals are enriched in Na and REE, and exhibit the following compositional range: (Ca 0.34–4.49 Sr 0.18–4.54 Na 0.05–0.30 REE 0.08–0.18 Ba 0–0.10)(P 2.87–3.03 Si 0–0.16)O 12 (F,OH). At Murun, in eastern Siberia, Russia, strontium-apatite also occurs in intimate association with strontian fluorapatite in a eudialyte-bearing nepheline syenite pegmatite. The overall compositional variation of these minerals can be expressed as (Ca 2.26–3.55 Sr 1.41–2.74 Na 0–0.03 REE 0–0..08)(P 2.91–3.01 Si 0– 0.06)O 12 (F,OH). At Lac de Gras, Northwest Territories, Canada, strontium-apatite and Sr-rich carbonate-hydroxylapatite compose cores of spherulites confined to vesicles in kimberlite, associated with suolunite and barian phlogopite. In addition to Sr, the apatite is enriched in Ba and V; the proportions of these elements decrease from the center of spherulites outward. The Lac de Gras apatite is inferred to contain carbon substituting for P. The overall compositional variation is (Sr 0.08–2.58 Ca 2.04–4.65 Ba 0– 0.21 Na 0.09–0.28 REE 0–0.07 K 0–0.03)(P 2.20–2.61 C ~0.25–0.50 Si 0.04–0.26 V 0–0.13)O 12 (OH,F). Sr-rich apatites (sensu lato) from peralkaline rocks and kimberlites differ in concentrations of minor components and evolutionary trends. The available data demonstrate that there is a continuous series of naturally occurring compositions from apatite to strontium-apatite with less than 7 mol.% Ca 5 (PO 4) 3 (F,OH). There are implications of these data for the crystal chemistry and nomenclature of apatite-group minerals.
Keywords: apatite; strontium-apatite; zoning; peralkaline rocks; kimberlites; Lovozero; Murun; Lac de Gras; Russia; Canada